Empirical Study of Social Media Marketing’s Impact on Brand Image and Loyalty in Retail, Muscat - Irfan Rais, Mohd (Mercados y Negocios, 2025)
This study aims to explore SMM’s influence on brand image and loyalty in the retail industry of Muscat. The study employs the quantitative method as it ensures valid and reliable results. The data for the analysis were collected from 150 employees in the retail sector through structured survey questionnaires. The data is analyzed using the SPSS tool through statistical approaches such as ANOVA, Correlation, and Regression. The findings of this research will illuminate the significance of SMM and identify factors that encourage SMM in the retail sector. The outcomes provide valuable insights into SMM initiatives that aid in increasing Muscat’s brand reputation and image in the retail industry. This study’s implications will benefit retail organizations in attaining a competitive advantage in the market.